Correction: The medicinal chemist's toolbox for late stage functionalization of drug-like molecules. (10th March 2017) - Cernak, Tim; Dykstra, Kevin D.; Tyagarajan, Sriram; Vachal, Petr; Krska, Shane W.
Abstract : Correction for 'The medicinal chemist's toolbox for late stage functionalization of drug-like molecules' by Tim Cernak et al., Chem. Soc. Rev., 2016, 45, 546–576.